Corona Ring Design Impact on the Electric Field Distribution Surrounding an Insulator String - Illias H.A.; Chean Y.S.; Ling L.Y.; Mokhlis H.; Ariffin A.M.; Yousof M.F.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Dielectric materials; Electric discharges; Electric grounding; Electric insulators; Electric power transmission; Porcelain; Rings (components); Transmissions; Corona discharges; Electric field distributions; Electric field magnitude; High voltage transmission lines; Insulator string; Outer diameters; Porcelain insulators; Transmission tower; Electric corona